Exploring Pathways to Recovery: A Comprehensive Literature Review on Mental Health Rehabilitation for Patients - Mohammed, Hadeel Hajjam Joher; Mouthar, Raeisa Mousa; Al-khawaji, Hana Ahmad Bhais; Alghamdi, Sara Husein Hasein; Aldosari, Amjad Nasser Ahmed; Alharbi, Fatima Abdullah Mohammed; Alotebi, Sarah Ghazi Hessen; Aghamdi, Hanin Saeed; Alharbi, Ghada Abdullah Mohammed; Assiri, Fatima Hassan (Journal of Ecohumanism, 2024)
Mental health rehabilitation is a critical component of the recovery process for individuals experiencing mental health challenges. This comprehensive literature review explores the diverse approaches to mental health rehabilitation, including psychosocial interventions, medical treatments, vocational programs, and the integration of digital tools. Emphasizing patient-centered care, the review highlights the importance of addressing individual needs, reducing stigma, and fostering social reintegration. Key barriers, such as limited resources and workforce challenges, are identified, alongside metrics for evaluating patient outcomes, including quality of life and clinical improvement. The review underscores the significance of tailored rehabilitation programs and calls for further research to bridge existing gaps and enhance the effectiveness of interventions.